Exploration of new models for primary dysmenorrhea treatment: low-power visible-light-activated photodynamic therapy and oral contraceptives - Wang, Yue; Chen, Jie; Zhang, Zhiyuan; Ding, Xuesong; Gan, Jingwen; Guo, Yingying; Liang, Wanqi; Wang, Yanfang; Deng, Yan; Sun, Aijun (Frontiers in Medicine, 2024)
Background Primary dysmenorrhea (PD) is one of the most common reasons that affect the life quality of women during childbearing age. This research aims to explore the efficacy and curative effect characteristics of oral contraceptives and low-power visible-light-activated photodynamic therapy (PDT). Besides investigating the possible mechanism of PDT, we expected to find a treatment model with better efficacy and fewer side effects. Method It was a multicenter, randomized, parallel-controlled study. Eligible participants were randomly assigned to three groups: placebo group, oral contraceptive (Marvelon) group, and the PDT group. They were treated continuously for three menstrual cycles and followed up for two cycles after treatment. The scores of the visual analog scale (VAS) and the concentration of pain-related small molecules in blood before and after treatment were recorded in each group, which can evaluate the therapeutic characteristics of different treatments. Result Both Marvelon and PDT were effective. The effect of Marvelon appears quickly which can significantly relieve symptoms at the beginning, while PDT shows a relatively slow role. There was no significant difference in the final efficacy two cycles after treatment. The therapeutic effect was achieved by reducing the concentrations of prostaglandin 2 (PGE2) and endothelin (ET) in the blood. Conclusion Marvelon and PDT are effective methods for the treatment of PD. The long-term efficacy of the two is similar, while the therapeutic characteristics and the side effects are different. Patients can choose the suitable way according to their individual needs.